Precision irrigation and fertilization strategies for sustainable cotton-wheat systems in water-scarce regions - Tarandeep Kaur; Pawan K. Sharma; A.S. Brar; Sukhpreet Singh; Surinder Singh (Agricultural Water Management)
Efficient irrigation and nutrient management are essential for sustaining agricultural productivity and enhancing water use efficiency in water-scarce agro-ecosystems. This two-year field study evaluated the integrated potential of sub-surface drip irrigation (SSDI), nitrogen fertigation, and foliar nutrient application to optimize water productivity and yield in a cotton-wheat cropping system (CWCS). A factorial randomized complete block design was employed, testing three irrigation levels—60 %, 80 %, and 100 % of crop evapotranspiration (ETc)—all applied through SSDI, along with two nitrogen fertigation rates (80 % and 100 % of the recommended dose), and two nutrient delivery methods (foliar spray vs. soil fertigation of KNO3 and MgSO4), alongside three control treatments (surface drip (SDI) and flood irrigation (FI)). SSDI at 80 % ETc achieved 7.97 % and 10.14 % higher productivity than 60 % ETc and FI respectively, while maintaining a yield comparable to 100 % ETc, thereby saving 20 % irrigation water without compromising performance. Compared to SDI and FI, it also reduced water use by 25 % and 36 %, respectively. Foliar nutrient application significantly improved crop (5.3 % higher) and water productivity (3.1 %) as well as profitability (2.6 % higher gross income and 2.7 % higher net income) over soil fertigation, while enabling nitrogen input reductions to 90 kg N ha−1 for cotton (from a recommended 112 kg ha−1) and 100 kg N ha−1 for wheat (from 125 kg ha−1), with sustained yields and improved input-use efficiency. Relative to flood irrigation, SSDI at 80 % ETc increased crop productivity by 8.2 %, apparent water productivity by 62.5 %, total water productivity by 6.2 % and partial factor productivity by 21.1 %. Additionally, SSDI at 80 % ETc resulted in 6.5 % higher gross returns and 5.2 % higher net returns compared to FI. These results underscore that integrating SSDI at 80 % ETc with reduced nitrogen fertigation, and foliar nutrient application offers a scalable, resource-efficient strategy for sustainable intensification of CWCS in semi-arid regions.